Visualizing Africa in Nineteenth-Century British Travel Accounts. - Koivunen, Leila (Routledge Research in Travel Writing, 2., 2008)
This study provides the first sustained analysis of the process by which images of Africa were transformed into the illustrations of the continent that appeared in nineteenth-century European travel books. Koivunen examines the actual production process of images and the books in which they were published in order to demonstrate how, why, and by whom the images were manipulated.